The usefulness of the fully tethered swimming for 50-m breaststroke performance prediction - Barbosa, A.; Dopsaj, M.; Okicic, T.; Andries Junior, O. (Biomechanics and Medicine in Swimming XI, 2010)
Propulsive force is well recognized as an important component of swimming performance, but most of the studies was focused on crawl-stroke and it is still unclear whether tethered swimming can be used to evaluate others strokes. The present study aimed to identify the relationship between 50-m breaststroke performance and force-time variables obtained from a 30-s maximal tethered swimming test. Fourteen highcompetitive male breaststrokers from Brazil and Serbia age: 22.50 ± 5.00 years, height: 1.83 ± 0.09 cm, weight: 76.3 ± 7.4 kg, percent from 50-m breaststroke long pool World Record: 91.91 ± 1.91%) accomplished a 30-s self-chosen cycle frequency maximal breaststroke effort in tethered swimming. The mean value of peak force (Fpeak), average force (Favg), impulse force (ImpF), rate o force development (RFD) and full stroke duration (DUR) was retained for analysis as independent variables. Time in 50m breaststroke was converted in average swimming velocity (VEL50m) to be used as dependent variable. The mean (±SD) values of VEL50m, Fpeak, Favg, ImpF, RFD and DUR were 1.72 ± 0.04 m/s, 469.82 ± 94.61 N, 136.92 ± 17.54 N, 156.52 ± 14.37 Ns, 1147.61 ± 464.55 N/s, 1157.65 ± 125.89, respectively. Multiple regression analysis with the backward method was employed to construct the model, which was statistically significant (F=29.933, p<0.001), explaining 82.1% of sample size adjusted variance (adjusted r²=0.821) with a standard error of ±0.015 m/s and represented the equation: VEL50m = 3.401 - 0.002*DUR + 0.015*ImpF - 0.015*Favg. The present results showed a high significant relationship between 50-m breaststroke performance and tethered swimming test, corroborating to previous study, which observed the same for high competitive crawl-strokers (Dopsaj et al., 2000), and confirming the initial hypothesis that the fully tethered swimming can be used for breaststroke performance evaluation and/or prediction. Besides, these results also allow to understand how much different each propulsive force variable is involved with swimming performance, what variables are needed to be improved for getting better results and, after testing swimmers at different moments of the periodization, identify deeper how the different training loads administrated are influencing performance in 50m breaststroke. Therefore, the fully tethered swimming can be used as a valid tool for breaststrokers` performance and evaluation.